Starch Bio-plastics for Packaging Application - Nasir , Nur Nadia; Othman, Siti Amira (Enhanced Knowledge in Sciences and Technology, 2023)
Bioplastics are made from either biodegradable and/or biobased material. The use of starch-based bioplastics in packaging has been limited due to a lack of water barrier qualities and poor mechanical capabilities. In recent year, there has been a lot of research done to improve the properties of starch-based bioplastics and one of the new technologies that have been introduced were gamma irradiation. Gamma irradiation is well- established process for modifying polymeric materials. As a result, this research was carried out to produce a corn-based bioplastic with the optimum glycerol-to-starch ratio, assess the effect of gamma radiation on corn-based bioplastic properties, and determine the feasibility of using irradiated corn-based bioplastic as a packaging material.